Online TESOL Teacher Education: outcome of a Pilot Project - Serafina Filice; Deana Bardetti (Je-LKS: Journal of E-Learning and Knowledge Society, 2018)
The increasing use of English throughout the world has seen the growth of career opportunities for teachers of English as a second language (ESL). In fact, there is a widespread demand for teachers with up-to-date qualifications in TESOL (Teaching English to Speakers of Other Languages). In addition, as teacher training is increasingly migrating from on-ground to online classrooms, there is a need to reach out to as many TESL teachers worldwide as possible. In fact, online education is expanding access to students internationally and domestically to students who would otherwise be unable to attend college (Christensen et al., 2011; Simpson, 2013). In this perspective, then, the online TESOL certificate program at Lesley University, Cambridge, MA aims at creating international partnerships with overseas teachers and promote the course. This article reports on the outcome of a pilot project that involved opening the online course to an Italian partner.